(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the present work the description of absorption spectra of ethidium bromide complexes with synthesized polyribonucleotide by several modes has been carried out. The binding constant value and the values of changes of thermodynamic parameters were determined. It was shown that at the description by linear binding isotherm the value of enthalpy and the number of nucleotides corresponding to one ligand molecule at interaction saturation are approximately the same as real ones, but the values of the binding constant, Gibbs free energy change and entropy change differ from real values.